Pengaruh Pemberian Latihan Wedge Terhadap Kemampuan Mengangkat Kepala Pada Posisi Tengkurap Bayi Usia 0-12 Minggu - Saputri, Isna Diah Dewi; , Agus Widodo SST.FT, M.Fis (2017)
Background: Prone position can encourage the development of head and neck extensor control, and motor development in infants. Babies are said to be able to lift his head when the baby is able to perform a movement raised his head and maintain the balance of his head in the prone position. The exercise program with a wedge into one of the interventions used to improve the ability to lift the head in the prone position babies aged 0-12 weeks. Objective: To determine the effect of exercise on the ability wedge lifted his head in a prone position babies aged 0-12 weeks. Method: The study was descriptive analytic with pre and post test with control group design, using the treatment group and the control group. Samples in the treatment group with a wedge given exercises 2 times a week for 5 minutes, while the control group was given no treatment with the wedge. The ability to lift the head was assessed by Alberta Infant Motor Scale (AIMS). Results: Delivery of exercise wedge in the group treated with 2 respondents showed an increase in the pre-test to post-test from grade 1 to grade 4. While in the control group with 2 respondents found two different results, on the one respondent there is an increase in the pre-test to post test from grade 1 to grade 3, respondents were not significantly increased pre-test to post-test of a grade from 0 to grade 1. Conclusion: There is a wedge effect of exercise on the ability to lift the head in the prone position babies aged 0-12 weeks.